Mutations at critical N-glycosylation sites reduce tyrosinase activity by altering folding and quality control. - Branza-Nichita, N; Negroiu, G; Petrescu, A; Garman, E; Platt, F; Wormald, M; Dwek, R; Petrescu, S (2000)
Tyrosinase is a copper-containing enzyme that regulates melanin biosynthesis in mammals. Mutations at a single N-glycosylation sequon of tyrosinase have been reported to be responsible for oculocutaneous albinism type IA in humans, characterized by inactive tyrosinase and the total absence of pigmentation. To probe the role that each N-glycosylation site plays in the synthesis of biologically active tyrosinase, we analyzed the calnexin mediated folding of tyrosinase N-glycosylation mutants. We have determined that four of the six potential N-glycosylation sites, including that associated with albinism, are occupied. Analysis of the folding pathway and activity of 15 tyrosinase mutants lacking one or more of the occupied N-glycosylation sites shows that glycans at any two N-glycosylation sites are sufficient to interact with calnexin and give partial activity, but a specific pair of sites (Asn(86) and Asn(371)) is required for full activity. The mutants with less than two N-glycosylation sites do not interact with calnexin and show a complete absence of enzyme activity. Copper analysis of selected mutants suggests that the observed partial activity is due to two populations with differential copper content. By correlating the degree of folding with the activity of tyrosinase, we propose a local folding mechanism for tyrosinase that can explain the mechanism of inactivation of tyrosinase N-glycosylation mutants found in certain pigmentation disorders.